High spatial resolution gene expression profiling and characterization of neuroblasts migrating in the peri-injured cortex using photo-isolation chemistry - Miyamoto, Takuya; Kuboyama, Kazuya; Honda, Mizuki; Ohkawa, Yasuyuki; Oki, Shinya; Sawamoto, Kazunobu (Frontiers in Neuroscience, 2025)
In the ventricular-subventricular-zone (V-SVZ) of the postnatal mammalian brain, immature neurons (neuroblasts) are generated from neural stem cells throughout their lifetime. These V-SVZ-derived neuroblasts normally migrate to the olfactory bulb through the rostral migratory stream, differentiate into interneurons, and are integrated into the preexisting olfactory circuit. When the brain is injured, some neuroblasts initiate migration toward the lesion and attempt to repair the damaged neuronal circuitry, but their low regeneration efficiency prevents functional recovery. Elucidation of the molecular basis of neuroblast migration toward lesions is expected to lead to the development of new therapeutic strategies for brain regenerative medicine. Here, we show gene expression profiles of neuroblasts migrating in the peri-injured cortex compared with those migrating in the V-SVZ using photo-isolation chemistry, a method for spatial transcriptome analysis. Differentially expressed gene analysis showed that the expression levels of 215 genes (97 upregulated and 118 downregulated genes) were significantly different in neuroblasts migrating in the peri-injured cortex from those migrating in the V-SVZ. Gene Ontology analysis revealed that in neuroblasts migrating in the peri-injured cortex, expression of genes involved in regulating migration direction and preventing cell death was upregulated, while the expression of genes involved in cell proliferation and maintenance of the immature state was downregulated. Indeed, neuroblasts migrating in the peri-injured cortex had significantly lower Cyclin D2 mRNA and Ki67 protein expression levels than those in the V-SVZ. In the injured brain, amoeboid microglia/macrophages expressed transforming growth factor-β (TGF-β), and neuroblasts migrating in the peri-injured cortex expressed TGF-β receptors. Experiments using primary cultured neuroblasts showed that application of TGF-β significantly decreased proliferating cells labeled with BrdU. These data suggest that the proliferative activity of neuroblasts migrating toward lesions is suppressed by TGF-β secreted from cells surrounding the lesion. This is the first comprehensive study characterizing the gene expression profiles of neuroblasts migrating in the peri-injured cortex.